3(4c+1)-17=2(3c+2)-3c

Simple and best practice solution for 3(4c+1)-17=2(3c+2)-3c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4c+1)-17=2(3c+2)-3c equation:


Simplifying
3(4c + 1) + -17 = 2(3c + 2) + -3c

Reorder the terms:
3(1 + 4c) + -17 = 2(3c + 2) + -3c
(1 * 3 + 4c * 3) + -17 = 2(3c + 2) + -3c
(3 + 12c) + -17 = 2(3c + 2) + -3c

Reorder the terms:
3 + -17 + 12c = 2(3c + 2) + -3c

Combine like terms: 3 + -17 = -14
-14 + 12c = 2(3c + 2) + -3c

Reorder the terms:
-14 + 12c = 2(2 + 3c) + -3c
-14 + 12c = (2 * 2 + 3c * 2) + -3c
-14 + 12c = (4 + 6c) + -3c

Combine like terms: 6c + -3c = 3c
-14 + 12c = 4 + 3c

Solving
-14 + 12c = 4 + 3c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-3c' to each side of the equation.
-14 + 12c + -3c = 4 + 3c + -3c

Combine like terms: 12c + -3c = 9c
-14 + 9c = 4 + 3c + -3c

Combine like terms: 3c + -3c = 0
-14 + 9c = 4 + 0
-14 + 9c = 4

Add '14' to each side of the equation.
-14 + 14 + 9c = 4 + 14

Combine like terms: -14 + 14 = 0
0 + 9c = 4 + 14
9c = 4 + 14

Combine like terms: 4 + 14 = 18
9c = 18

Divide each side by '9'.
c = 2

Simplifying
c = 2

See similar equations:

| 5=7x-2 | | (7.29)(0.6+0.7)= | | 3(2x+1)=5 | | 7x-5y=-19 | | -3x+6=-27 | | y=0.3-2 | | (3w+5)(3w-5)= | | .5x+.40(400)=.10(x+400) | | 2x(-10)+y(-11)=180 | | -3x+6=-24 | | .5x+.30(400)=.10(x+400) | | -5x+8=-7 | | -8x^2-39x+5=0 | | 2x-10+y-11=180 | | 64+27=97+x | | 6-7(a+1)-7x=6+5x-2 | | 4x+2y=43 | | 8x-10=22+4x | | 14+x=2-2x | | 5x-5(6x-8)=-135 | | 6h-(-34)=-6h+14 | | -m/2+7=21 | | 12=2x^2-3x+7 | | 3x+8+x-13+x=180 | | -165.832=-10.9k | | 32y^4-48y^3+18y^2= | | -3(p-2)=12 | | 50.24=2(3.14)r | | 5c-6=11 | | 3x+8=x-13 | | 50.24=2(314)r | | 6x^2+x-51=0 |

Equations solver categories